Examining the Importance of Effective Human Resources Planning (HRP) in Optimizing Organizational Performance - Bahiroh, Eloh (Management Science Research Journal, 2024)
In an increasingly dynamic business environment, effective human resource planning (HRP) has emerged as a critical factor in driving organizational performance, though gaps remain in understanding HRP as a direct contributor to strategic outcomes. This study aims to assess the impact of HRP practices—workforce forecasting, talent management, and succession planning—on productivity, employee retention, and adaptability. A mixed-methods approach was employed, combining quantitative analysis of performance metrics from 200 organizations with qualitative insights from in-depth interviews with HR managers. Results indicate a strong positive correlation between HRP practices and organizational performance, with workforce forecasting contributing significantly to stability, and talent management and succession planning driving engagement and continuity. The study also highlights adaptability as a crucial element for HRP, particularly in volatile industries. These findings suggest that HRP, when strategically aligned, not only enhances competitive advantage but also provides resilience to organizational shifts. This research contributes a novel perspective by positioning HRP as a core strategic function, offering practical recommendations for optimizing HRP practices in response to emerging business challenges. The study’s insights serve as a foundation for future research on adaptive HR strategies in dynamic market conditions